Notions of relevance for modeling the dynamics of belief - Falappa, Marcelo Alejandro (2001)
We identify different kinds of relevance relations between formulas that emerge in the process of belief revision. Informal definitions for alternative notions of relevance are suggested and a set of schemas and intuitive postulates for formalizing these notions are proposed. The notions of relevance proposed here are shown to be good candidates for modeling the process of belief revision.